2011
DOI: 10.1586/edm.11.10
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric aspects of skin disorders

Abstract: The skin is recognized as an important mode of communication between the external and the internal psychic and biological processes [1]. The skin and the psyche are closely related from historical, embryologic, biological, psychological developmental and cultural perspectives.The importance of the skin is that it is literally the initial point of contact between the external and internal environments. Exposure to external pollutants, toxins, allergens and other noxious environmental elements find symptomatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
1
14
0
6
Order By: Relevance
“…Several dermatological conditions have been reported in association with psychological stress such as psoriasis, alopecia areata, atopic dermatitis, lichen planus, pruritus and rosacea. Moreover, emotional stress may exacerbate many chronic dermatologic conditions and can also lead to initiation of a vicious cycle referred to as "itchscratch cycle" [1] [2]. Psychiatric and psychological factors are thought to play a role in at least 30% of dermatologic disorders [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several dermatological conditions have been reported in association with psychological stress such as psoriasis, alopecia areata, atopic dermatitis, lichen planus, pruritus and rosacea. Moreover, emotional stress may exacerbate many chronic dermatologic conditions and can also lead to initiation of a vicious cycle referred to as "itchscratch cycle" [1] [2]. Psychiatric and psychological factors are thought to play a role in at least 30% of dermatologic disorders [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] An international multicentre cross-sectional study across 13 European countries found that 10.1% and 17.2% of dermatology patients suffered from depression and anxiety, respectively. 4 When compared to healthy controls or the general population, dermatology patients are more likely to suffer from anxiety and depression; in a Norwegian study, 13% versus 3.7% and 5.8% versus 0.9% of dermatology patients versus controls suffered from anxiety and depression, respectively.…”
mentioning
confidence: 99%
“…The fact that we studied cosmetology patients could also account for high psychological morbidity as cosmetic concerns can lead to self -derogatory feelings, embarrassment and social isolation. 1 Majority of the patients in the current study had a college degree and belonged to urban areas. This indicates that higher the education and awareness, more is the concern regarding physical appearance leading to medical consultation.…”
Section: Results and Discussion Figmentioning
confidence: 86%
“…The psychological effect of cosmetic concerns on patients can include embarrassment, frustration, low self-esteem, dissatisfaction with appearance, difficulty in social interactions with the opposite gender, shyness in appearances in public and reduced employment opportunities. 1,2 Psychodermatology is an emerging arena in dermatology which deals with its interface with psychiatry. How a patient reacts to a dermatological or cosmetic concern can be an interesting and complex interaction between the dermatological lesion, internal factors such as patients' attitude or personality traits and external factors such as social stigma or life stressors.…”
Section: Introductionmentioning
confidence: 99%